The Dilemma of Auditors’ Professional Ethics in Enhancing Audit Effectiveness - Nur Sakinah Irman; Sumarlin; Della Fadhilatunisa (Academic Bright Collaboration, 2026)
This study examines the professional ethical dilemmas faced by internal auditors within the Internal Supervisory Unit (SPI) at UIN Alauddin Makassar and their impact on the effectiveness of internal audits. This research employs a qualitative method with a phenomenological approach, and data were collected through interviews. The findings reveal that the dual roles of auditors can actually create a positive synergy between academic responsibilities and internal audit functions. Auditors face negative stigma from auditees, who perceive them as